A pro-tumorigenic function of S100A8/A9 in carcinogen-induced hepatocellular carcinoma. Issue 2 (28th December 2015) - De Ponti, Aurora; Wiechert, Lars; Schneller, Doris; Pusterla, Tobias; Longerich, Thomas; Hogg, Nancy; Vogel, Arndt; Schirmacher, Peter; Hess, Jochen; Angel, Peter
Abstract: Human hepatocellular carcinoma (HCC) is a heterogeneous disease, driven by different risk factors and presenting diverse clinicopathological features and outcomes. Epidemiological and experimental data indicate that the damage-associated molecular pattern molecules S100A8 and S100A9, forming a heterodimer called calprotectin, might be critically involved in HCC development. However, deletion of S100a9 in an inflammation- and cirrhosis-driven mouse model did not show any impairment in liver tumorigenesis, most likely due to functional compensation by other inflammatory cytokines. Here, we investigated the effect of calprotectin ablation in mice treated with diethylnitrosamine, a carcinogen-driven HCC model mimicking cancer development caused by acute liver damage in the absence of prominent chronic inflammation and tissue damage. We found that tumor cell proliferation was diminished in the absence of S100A8/A9, leading to significant reduction of tumor size. Our results demonstrate that calprotectin is required for the progression of non-inflammation driven liver tumor and might represent a therapeutic target for the treatment of HCC formed in non-cirrhotic liver.